Effet d'un pilotage par les instruments sur l'activité des formateurs d'enseignants - Pierre-Alain Filippi (Nantes Université, 2022)
The history of teacher training in France has been marked by reforms accompanying major changes in society. The pace of change has accelerated considerably since 1989. This phenomenon of permanent reform is part of a wider movement of governance which considers that public action in the State is managed more effectively if the same methods and management tools are applied as in the business world.In this article we will mobilise the concept of instrumentation of public action to show how the introduction of a new device whose prescription is mainly instrumental affects the activity of teacher trainers in an "école supérieure du professorat et de l'éducation" (ESPE) in the south of France and in what way. We will also show, on the basis of some results, how the implementation of an intervention-research in this work environment contributed to giving the teacher trainers involved new possibilities of acting.